627 The DLL3-targeted half-life extended bispecific T cell engager (HLE BiTE®) immune-oncology therapy AMG 757 has potent antitumor activity in neuroendocrine cancer. (10th December 2020) - Cooke, Keegan; Estrada, Juan; Zhan, Jinghui; Werner, Jonathan; Lee, Fei; Shetty, Aditya; Smit, Marie-Anne Damiette; Salvati, Mark; Bailis, Julie
Abstract : Background: Neuroendocrine tumors (NET), including small cell lung cancer (SCLC), have poor prognosis and limited therapeutic options. AMG 757 is an HLE BiTE® immune therapy designed to redirect T cell cytotoxicity to NET cells by binding to Delta-like ligand 3 (DLL3) expressed on the tumor cell surface and CD3 on T cells. Methods: We evaluated activity of AMG 757 in NET cells in vitro and in mouse models of neuroendocrine cancer in vivo. In vitro, co-cultures of NET cells and human T cells were treated with AMG 757 in a concentration range and T cell activation, cytokine production, and tumor cell killing were assessed. In vivo, AMG 757 antitumor efficacy was evaluated in xenograft NET and in orthotopic models designed to mimic primary and metastatic SCLC lesions. NSG mice bearing established NET were administered human T cells and then treated once weekly with AMG 757 or control HLE BiTE molecule; tumor growth inhibition was assessed. Pharmacodynamic effects of AMG 757 in tumors were also evaluated in SCLC models following a single administration of human T cells and AMG 757 or control HLE BiTE molecule. Results: AMG 757 induced T cell activation, cytokine production, and potent T cell redirected killing of DLL3-expressing SCLC, neuroendocrine prostate cancer, and other DLL3-expressing NET cell lines in vitro. AMG 757-mediated redirected lysis was specific for DLL3-expressing cells. In patient-derived xenograft and orthotopic models of SCLC, single-dose AMG 757 effectively engaged human T cells administered systemically, leading to a significant increase in the number of human CD4+ and CD8+ T cells in primary and metastatic tumor lesions. Weekly administration of AMG 757 induced significant tumor growth inhibition of SCLC (figure 1 ) and other NET, including complete regression of established tumors and clearance of metastatic lesions. These findings warranted evaluation of AMG 757 (NCT03319940 ); the phase 1 study includes dose exploration (monotherapy and in combination with pembrolizumab) and dose expansion (monotherapy) in patients with SCLC (figure 2 ). A study of AMG 757 in patients with neuroendocrine prostate cancer is under development based on emerging data from the ongoing phase 1 study. Conclusions: AMG 757 engages and activates T cells to kill DLL3-expressing SCLC and other NET cells in vitro and induces significant antitumor activity against established xenograft tumors in mouse models. These preclinical data support evaluation of AMG 757 in clinical studies of patients with NET. Ethics Approval: All in vivo work was conducted under IACUC-approved protocol #2009-00046.